Reflecting Journeys: Student Nurses’ Perceptions of Their Reflective Practices - Dayang Zuraina, Abang Haji Kashim (Malaysian Nurses Association, 2020)
Background: Reflective practice is deemed significant in nursing education, and it is important that nursing students be encouraged to learn how to think critically and be more innovative. Those who acknowledge the importance of promoting reflective practice in nursing education, are starting to use journals practice tools for reflection. However, it is still unclear as to what extent these students comprehend the practice of reflection, how they feel about it, and whether journal writing actually aids in acquiring skills of reflection.